A comparative study on the dissolution and stability of beudantite and hidalgoite at pH 2–12 and 25–45 °C for the possible long-term simultaneous immobilization of arsenic and lead. (January 2021) - Yinian Zhu,; Wei, Wanying; Tang, Shen; Zhu, Zongqiang; Yan, Qiming; Zhang, Lihao; Deng, Huan
Abstract: Beudantite and hidalgoite were synthesized and characterized to investigate their possible immobilization for arsenic and lead in acidic and oxidizing environments by a long-term dissolution. The synthetic beudantite [Pb0.35 (H3 O)0.40 Fe3.09 (AsO4 )0.37 (SO4 )1.63 (OH)6.00 ] was spherulitic pseudo-cubic crystals with nearly smooth surface. The synthetic hidalgoite [Pb0.72 (H3 O)2.71 Al2.26 (AsO4 )0.93 (SO4 )1.07 (OH)6.00 ] was well-formed pseudo-cubic, pseudo-cuboctahedral or pseudo-octahedral crystals. During the beudantite dissolution, the constituents were dissolved preferentially in the order of SO4 2−  > AsO4 3−  > Pb 2+  > Fe 3+ in the early 24 h and SO4 2−  > AsO4 3−  > Fe 3+  > Pb 2+ after 24 h; the dissolved concentrations exhibited a minimum of 0.0027–0.0030 mg/L Pb and 0.0248–0.0250 mg/L As. During the hidalgoite dissolution, the constituents were dissolved preferentially in the order of Pb 2+  > SO4 2−  > AsO4 3−  > Al 3+ at initial pH < 4 or AsO4 3−, SO4 2−  > Al 3+  > Pb 2+ at initial pH > 4; the dissolved concentrations showed a minimum of 0.0055–0.0061 mg/L Pb and 0.0750–0.0810 mg/L As. From the data of the dissolution at initial pH 2 and 25 °C for 270–330 d, the ion-activity products [logˍIAP] were estimated to be −94.18 ± 0.04 for the beudantite and −73.82 ± 0.11 for the hidalgoite, respectively. The concentrations of Pb and As released in the beudantite dissolution were always lower than in the hidalgoite dissolution and arsenate appeared to be much more soluble than Pb. Beudantite was more effective for the immobilization of As and Pb than hidalgoite. Graphical abstract: Image 1 Highlights: The synthetic beudantite & hidalgoite were mainly well-formed pseudo-cubic crystal. Sulfate/arsenate were preferentially released in dissolution compared to Fe/Al. Arsenate appeared to be much more soluble than lead in dissolution. Beudantite was more suitable for the immobilization of As and Pb than hidalgoite. The logˍIAPs were −94.18 ± 0.04 for beudantite and −73.82 ± 0.11 for hidalgoite.